Literature Review Human Resource Management: Strategy, Evaluation, and Development - Suprapto, Eko (International Journal of Advanced Multidisciplinary, 2022)
Human resource management is a very important aspect in general. Therefore, the functions in the management of human resources must be carried out optimally so that the needs concerning individual, company, organizational or institutional goals can be achieved. In addition, with good human resource management procedures, it is hoped that the shortcomings and problems faced by the Indonesian people, namely those related to competitiveness, can be overcome. One proof that the Indonesian nation is still not ready to compete in the global world can be seen from the competitiveness of its human resources. The results of the article are: 1) Strategy has an effect on HR Management; 2) Evaluation has an effect on HR Management; and 3) Development has an effect on HR Management